Analisis Kandungan Vitamin Pada Melon (Cucumis melo L.) Kultivar Melodi Gama 1 dan Melon Komersial - Budi S Daryono; Sigit Dwi Maryanto; Sholihatun Nissa; Ganies Riza Aristya (Biogenesis: Jurnal Ilmiah Biologi, 2016)
As many as 50 million people worldwide are currently experiencing a deficiency of vitamin A and about 250000-500000 malnourished children in developing countries become blind each year from vitamin A deficiency, with the highest prevalence in Southeast Asia and Africa which will result in visual impairment, and increased child mortality and pregnant women. Melon can be one of the solutions for higher productivity and fruit may contain carotene (pro-vitamin A) with varying levels. In the years 2009-2011 Genetics laboratory, faculty of Biology UGM has produced a new melon cultivar called Melodi Gama 1 (MG 1). MG 1 phenotype has a rounded character with rather thick rind and hard, green and fleshy with a smooth orange flesh color. The purpose of this research was to study and analyze the nutritional content of MG 1 compared to commercial cultivars from multilocation and multiseason cultivation. The methods were used vitamin A quantitative analysis by extraction and spectrophotometer, whereas vitamin C in quantitative analysis using the iodine titration method. The results obtained in the analysis of total carotene in the dry season for the MG 1 has the highest value compared with 4 other commercial cultivars, it was 706.61 μg/100gr for cultivation in Yogyakarta and 292.16 μg/100gr for cultivation in Magetan. In the rainy season total carotene MG 1 was 59.88 μg/100gr for cultivation in Yogyakarta, and 20.76 μg/100gr for cultivation in Magetan. The results of the quantitative analysis of vitamin C MG 1 in the dry season was 7.50 mg/100gr for cultivation in Yogyakarta and 16.50 mg/100gr for cultivation in Magetan, while the rainy season was 8.55 mg/100gr for cultivation in Yogyakarta and 6.75 mg/100gr for cultivation in Magetan. Based on these results it can be concluded that the content of Vitamin A and C from Melodi Gama 1 cultivar is higher in the dry season than in the rainy season.